Significance of nitric oxide synthases: Lessons from triple nitric oxide synthases null mice - Masato Tsutsui; Akihide Tanimoto; Masahito Tamura; Hiroshi Mukae; Nobuyuki Yanagihara; Hiroaki Shimokawa; Yutaka Otsuji (Elsevier, 2015)
Nitric oxide (NO) is synthesized by three distinct NO synthases (neuronal, inducible, and endothelial NOSs), all of which are expressed in almost all tissues and organs in humans. The regulatory roles of NOSs in vivo have been investigated in pharmacological studies with non-selective NOS inhibitors. However, the specificity of the inhibitors continues to be an issue of debate, and the authentic significance of NOSs is still poorly understood. To address this issue, we generated mice in which all three NOS genes are completely disrupted. The triple NOSs null mice exhibited cardiovascular abnormalities, including hypertension, arteriosclerosis, myocardial infarction, cardiac hypertrophy, diastolic heart failure, and reduced EDHF responses, with a shorter survival. The triple NOSs null mice also displayed metabolic abnormalities, including metabolic syndrome and high-fat diet-induced severe dyslipidemia. Furthermore, the triple NOSs null mice showed renal abnormalities (nephrogenic diabetes insipidus and pathological renal remodeling), lung abnormalities (accelerated pulmonary fibrosis), and bone abnormalities (increased bone mineral density and bone turnover). These results provide evidence that NOSs play pivotal roles in the pathogenesis of a wide variety of disorders. This review summarizes the latest knowledge on the significance of NOSs in vivo, based on lessons learned from experiments with our triple mutant model.